Surface-wave pulse routing around sharp right angles - Gao, Zhen (2018)
Surface-plasmon polaritons (SPPs), or localized electromagnetic surface waves propagating on a metal-dielectric interface, are deemed promising information carriers for future subwavelength terahertz and optical photonic circuitry. However, surface waves fundamentally suffer from scattering loss when encountering sharp corners in routing and interconnection of photonic signals. Previous approaches enabling scattering-free surface-wave guidance around sharp corners are limited to either volumetric waveguide environments or extremely narrow bandwidth, being unable to guide a surface-wave pulse (SPP wave packet) on an on-chip platform. Here, in a surface-wave band-gap crystal implemented on a single metal surface, we demonstrate in time-domain routing a surface-wave pulse around multiple sharp right angles without perceptible scattering. Our work not only offers a solution to on-chip surface-wave pulse routing along an arbitrary path, but it also provides spatiotemporal information on the interplay between surface-wave pulses and sharp corners, both of which are desirable in developing high-performance large-scale integrated photonic circuits.